Offender Based Transaction Statistics (OBTS), 1987: Alabama, Alaska, California, Delaware, Georgia, Minnesota, Missouri, Nebraska, New Jersey, New York, Pennsylvania, Utah, Vermont, and Virginia ([Verlag nicht ermittelbar], 1990)
Offender Based Transaction Statistics (OBTS) studies are designed to collect information by tracking adult offenders from the point of entry into the criminal justice system (typically by arrest) through final disposition, regardless of whether the offender is convicted or acquitted. Information is provided on arrest, police action, prosecutor action, level of charges, charges filed by the prosecutor, type of counsel, pretrial status, type of trial, sentence type, and sentence length. This allows researchers to examine how the criminal justice system processes offenders, to measure the changing volume of offenders moving through the different segments of the criminal justice system, to calculate processing time intervals between major decision-making events, and to assess the changing structure of the offender population.